Efficacy of a Dietary Supplement Extracted from Persimmon (Diospyros kaki L.f.) in Overweight Healthy Adults: A Randomized, Double-Blind, Controlled Clinical Trial - Silvia Pérez-Piñero; Juan Carlos Muñoz-Carrillo; Jon Echepare-Taberna; Cristina Herrera-Fernández; Macarena Muñoz-Cámara; Vicente Ávila-Gandía; Francisco Javier López-Román (Foods)
A single-center, randomized, double-blind, and placebo-controlled clinical trial assessed the efficacy in improving body composition and in weight management of a dietary supplement consisting of 400 mg of a standardized extract of the persimmon fruit (Diospyros kaki L.f.) in adult subjects with a BMI between 25 and 34.99 kg/m2 administered for 120 consecutive days. In total, 36 participants were assigned to the placebo group and 35 to the experimental group (registered at ClinicalTrials.gov (NCT05750342)). Primary analysis focused on overweight subjects (placebo, n = 26; experimental, n = 23). In this group, fat mass expressed in kg and percentage evaluated by both dual-energy X-ray absorptiometry (DEXA) and bioelectrical impedance analysis (BIA) decreased significantly (between-group differences p < 0.001) in those receiving the persimmon extract as compared with the placebo. No significant reduction in lean mass was observed, suggesting that the muscle mass was maintained during fat loss. The use of the investigational product improved classic anthropometric parameters to a statistically significantly greater extent than the placebo, including body weight, BMI, and waist and abdominal circumference (p < 0.001), in the overweight group. In the overall population, similar improvements were observed, with significant between-group differences (p < 0.001) in fat mass reduction and improvements in body composition. Changes in the biochemical lipidic, glycemic, and anti-inflammatory profile were not found, except for between-group significant differences (p < 0.001) in decreases in tumor necrosis factor-alpha (TNFα) and increases in total antioxidant capacity (TAC) in favor of the experimental condition. There was a significant increase in fecal fat excretion in the experimental group at the end of the study in subjects with low fecal fat (9%) at baseline. Consumption of the investigational product vs. placebo improved the quality of life, with significantly greater scores in the total score and the mental health component of the SF-12 questionnaire. The persimmon extract was safe and well tolerated.